The Chemical Constituents of Ficus benjamina Linn. and Their Biological Activities - Dafalla, Hassan Abdalla Almahy; Rahmani, Mawardi; Sukari, Mohd Aspollah; Ali, Abdul Manaf (Universiti Putra Malaysia Press, 2003)
The leaves, bark and fruits of Ficus benjamina Linn. were subjected to extraction and isolation using chromatographic techniques to yield six compounds (cinnamic acid, lactose, naringenin, quercetin, caffeic acid and stigmasterol). The structures of the compounds were determined by spectroscopic techniques and by comparison with published data. The compounds were screened for antimicrobial activity against two species of bacteria (Bacillus cereus and Pseudomonas aeruginosa) and cytotoxic activity against T-lyrnphoblastic leukemic (CEM-SS) cell line. Caffeic acid exhibited strong cytotoxic activity with IC 50 value of 25 mg/mL.